Kin do not always help: testing multiple hypotheses on nest feeding in a cooperatively breeding bird. (18th August 2022) - Cousseau, Laurence; Van de Loock, Dries; Apfelbeck, Beate; Githiru, Mwangi; Matthysen, Erik; Lens, Luc
Abstract: In cooperatively breeding species, group members may derive multiple benefits from helping to raise other individuals' offspring, yet not all individuals do so. In this study, we tested predictions from the "kin selection", "pay-to-stay", "group augmentation" and "skills" hypotheses, to explain why group members feed nestlings of breeding placid greenbuls ( Phyllastrephus placidus ). In our study population, about 70% of the breeding pairs were accompanied by subordinates, and in 60% of these cases at least one subordinate helped in provisioning nestlings. In total, 80% of the subordinates were related to one or both breeders. In accordance with the "kin selection" hypothesis, and contrary to the "pay-to-stay" hypothesis, all the helpers were first-order kin of the breeding female (although relatedness to the breeding male did not explain variation in helping) and the presence of helpers was associated with increased survival of the breeding pair. However, the propensity to help varied among group members, as 46% of group members related to the breeding female did not feed nestlings. Younger helpers fed offspring more often than older ones, supporting the "skills" and "group augmentation" hypotheses. However, support for the "group augmentation" hypothesis was mixed since subordinate sex and group size did not explain additional variation in helping propensity and effort. We argue that in addition to indirect and direct benefits, also the costs of helping as well as other types of helping aside from provisioning must be considered to better understand variation in helping behavior. Abstract : Relatedness is thought to be an important factor explaining helping at the nest by non-breeding group members. We show that placid greenbul helpers are always related to the breeding females, supporting this view. However, many related groups members never helped suggesting that other factors shape helping decision in this species.